Guidelines for conducting capacity needs assessments in IFPRI’s policy research and outreach programs - Babu, Suresh Chandra (International Food Policy Research Institute, 2017)
Capacity challenges thwart economic growth and development. Efforts to strengthen capacity can benefit from past lessons and documented best practices. This note provides an overview of best practices for one of the key elements of capacity development—namely, the capacity needs assessment. Capacity strengthening is a broad concept that is widely used in the field of development. One commonly used definition of capacity strengthening in the literature comes from the United Nations Development Program (UNDP). UNDP defines capacity strengthening as the “process through which individuals, organizations, and societies obtain, strengthen, and maintain capabilities to set and achieve their own development objectives over time” (UNDP 2008).